Effective Factors on Sexual Quality of Life in Iranian Women: A Path Model - Sheikhan, Zohre; Ozgoli, Giti; Zahiroddin, Alireza; Khodakarami, Nahid; Nasiri, Malihe; Kavosi, Fahimeh (Advances in Nursing & Midwifery, 2019)
Introduction: Sexual affairs are one of the physiological needs affecting human health. Sexual functioning disorders can reduce individual’s capabilities and creativities. Sexual relations are in the center of women’s quality of life. This study aimed to investigate the correlation of sexual violence, stress perceived, demographic characteristic of women and high risk behavior spouse with sexual quality life of women by using Path model in Iranian women who referred to health centers affiliated to Shahid Beheshti University of Medical Sciences Tehran, Iran in 2015. Methods: This was sectional descriptive-correlative study conducted on 800 women who were selected through multistage sampling method. Data were collected through distinct questionnaires demographic characteristics ,sexual quality life of female(SQOL-F) , sexual violence, stress perceived and high risk behavior spouse that completed by interview .Software SPPS16 and LISREL8.80 used for analysis of data. Results: The results revealed that among direct pathways, sexual violence (β = -0.40) was the most effective predictor of sexual quality of life women. The age (β=-0.03 ) had an inverse association with sexual quality of life women through direct effect of sexual violence(β=0.33). Moreover, education (β=0.03) had a direct association with sexual quality of life women through inverse association 0f sexual violence (β=-0.10). Stress perceived ( β=-0.24) and high risk behavior spouse (β=-0.30) indirectly, effects on sexual quality of life women. Conclusion: Women have the rights to experience a safe and enjoyable sexual relationship. Sexual function is very complicated and is affected by many factors, including the personal lifestyle and interpersonal relationships. It is essential that noticed to sexuality and increase quality marital life but avoidance of high risk behaviors will help to it. Keywords: Sexual Quality, Sexual violence, Stress perceived , High risk behavior, Women, Iran